Post-operative complications rates in patients undergoing emergency laparotomy in tertiary care hospital - Gangamma, K; Manoj, P; Shashikumar, HB (Asian Journal of Medical Sciences, 2022)
Background: Post-operative complication may occur after explorative laparotomy whether elective or emergency. This study was aimed to evaluate the cause in which emergency laparotomy has been done, the frequency of different types of surgical complications after laparotomy in KR hospital, Mysore Medical college and Research Institute, Mysore, Karnataka. Aims and Objective: This study aims to evaluate the post-operative complications in patients undergoing emergency laparotomies at K R Hospital, Mysore Medical College and Research Institute, Mysore. Materials and Methods: This prospective observational study was carried out at the Department of General Surgery in Mysore Medical College, Mysore, Karnataka, during the period of October 2020–June 2021. All the patients who underwent emergency laparotomy were included in the study. They were followed up in the post-operative period and all the complications/sequelae developed were recorded. Results: The primary indications for an exploratory laparotomy are perforation peritonitis constituted (58.8%) cases followed by intestinal obstruction (13%), gallbladder perforation (10%), blunt and penetrating trauma abdomen (9.2%), and appendicular abscess/perforation (4.8%). In this study, most of the patients (77.2%) were between 21 and 50 years of age. Out of these, maximum cases (age) were found in the 4th decade, that is, 107 cases (42.8%). In this study local complication, surgical site infection (47.2%) was the most common complication followed by respiratory infection (30%), fever (38%), nausea and vomiting (14%), paralytic ileus (12.8%), UTI (10%), and thrombophlebitis (10.8%). Mortality was 6%. Conclusion: Post-operative complications are more common after emergency laparotomy as compared to elective laparotomies. Post-operative surgical site infection, nausea and vomiting, and fever are the most common complications which need adequate management and post-operative care.